Thiodigalactoside shows antitumour activity by beta‐galactoside‐binding protein and regulatory T cells inhibition in oral squamous cell carcinoma. (26th April 2016) - Aggarwal, S; Das, SN
Abstract : Objective: Thiodigalactoside (TDG), a synthetic inhibitor of β ‐galactoside‐binding protein (β ‐GBP) suppresses tumour growth by inhibiting multiple cancer enhancing activities of β ‐GBP. Hence, we attempted to understand whether disruption of β ‐GBP functions and indirect inhibition of Treg cells by TDG affect the growth and establishment of oral cancer cells. Method: The growth, morphology, cell cycle regulation, apoptosis induction and angiogenesis of oral cancer cell lines (SCC‐4, SCC‐9, SCC‐25) via MACS‐purified Treg cells were performed by MTT, propidium iodide (PI) staining, annexin‐V‐binding assay and ELISA respectively. Results: Treatment with β ‐GBP showed growth‐promoting effects on Tregs and oral cancer cells. However, the treatment with its inhibitor TDG resulted in inhibition of Treg subsets and also decreased the frequency of IL10 + and IL35 + Tregs indicating its immunomodulatory effects. Additionally, TDG treatment significantly ( P  < 0.001) inhibited the growth of OSCC cells with a concomitant induction of apoptosis, cell cycle arrest and anti‐angiogenesis. Conclusion: It appears that TDG concurrently prevents many tumour‐promoting effects of β ‐GBP in oral cancer cells possibly by Treg inhibition. This offers a preclinical proof of the concept that therapeutic targeting of β ‐GBP can overcome Treg ‐mediated tumour promotion and immunosuppression in oral cancer patients.